Attachment Networks in Committed Couples - Carli, Lucia L.; Anzelmo, Elena; Pozzi, Stefania; Feeney, Judith A.; Gallucci, Marcello; Santona, Alessandra; Tagini, Angela (Frontiers in Psychology, 2019)
This study explored attachment networks in long-term couples who differed in parenting choice and relationship status. Attachment networks were defined in terms of attachment functions, attachment strength, the presence of a primary figure, and full-blown attachments. Participants were 198 couples, married or cohabiting, either expecting their first child or childless-by-choice. Results indicated that partners were the most significant figures on all indicators. However, expectant women reported more proximity seeking and stronger attachments to mothers, while expectant men relied more on fathers for safe haven. Married participants indicated less proximity seeking to partners than cohabiting couples, and married women reported less reliance on partners for safe haven than married men and cohabiting women. This study supports previous findings underlining the particular importance of partners for members of long-term couples. Further, it extends past research by showing the robustness of this finding across parenting choice, and by revealing gender differences in the attachment networks of committed couples.